2022
DOI: 10.3390/ijerph192416973
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization and Quality of Life among Chinese Adolescents: An Integrative Analysis of Internet Addiction and Social Withdrawal

Abstract: Bullying victimization has been proven to be a direct predictor of adolescents’ quality of life, whereas elaborate mechanisms remain inconclusive. This study aims to explore the mediating pathway of Internet addiction and social withdrawal on the relationship between bullying victimization and quality of life among Chinese adolescents. This study used the cross-sectional data collected by self-reported questionnaires, including multidimensional peer-victimization scale, youth quality of life instrument-short f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Chinese researchers Gao and Chen demonstrate that Internet addiction is a dependent behavior caused by psychological mechanisms [ 15 ]. The studies found that IA causes a certain degree of negative impact on secondary school student’s academic development and mental health and is an influential driver of boredom and withdrawal from school for students currently [ 16 , 17 ], which leads to the rising occurrence of depression and loneliness [ 18 ] even to the emergence of non-suicidal self-injurious behavior [ 19 ]. A statistical analysis from December 2021 highlighted that 13.3% of internet users between the ages of 10 to 19 are affected [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese researchers Gao and Chen demonstrate that Internet addiction is a dependent behavior caused by psychological mechanisms [ 15 ]. The studies found that IA causes a certain degree of negative impact on secondary school student’s academic development and mental health and is an influential driver of boredom and withdrawal from school for students currently [ 16 , 17 ], which leads to the rising occurrence of depression and loneliness [ 18 ] even to the emergence of non-suicidal self-injurious behavior [ 19 ]. A statistical analysis from December 2021 highlighted that 13.3% of internet users between the ages of 10 to 19 are affected [ 20 ].…”
Section: Introductionmentioning
confidence: 99%